Neuronal C‐Reactive Protein/FcγRI Positive Feedback Proinflammatory Signaling Contributes to Nerve Injury Induced Neuropathic Pain. Issue 10 (2nd February 2023) - Liu, Fan; Zhang, Li; Su, Si; Fang, Yehong; Yin, Xiang‐sha; Cui, Huan; Sun, Jianru; Xie, Yikuan; Ma, Chao
Abstract: Neuropathic pain is difficult to treat in clinical practice, and the underlying mechanisms are insufficiently elucidated. Previous studies have demonstrated that the neuronal Fc‐gamma‐receptor type I (Fc γ RI) of the dorsal root ganglion (DRG) mediates antigen‐specific pain. However, the mechanisms of neuronal Fc γ RI in neuropathic pain remain to be explored. Here, it is found that the activation of Fc γ RI‐related signals in primary neurons induces neuropathic pain in a rat model. This work first reveals that sciatic nerve injury persistently activates neuronal Fc γ RI‐related signaling in the DRG, and conditional knockout (CKO) of the Fc γ RI‐encoding gene Fcgr1 in rat DRG neurons significantly alleviates neuropathic pain after nerve injury. C‐reactive protein (CRP) is increased in the DRG after nerve injury, and CRP protein of the DRG evokes pain by activating neuronal Fc γ RI‐related signals. Furthermore, microinjection of naive IgG into the DRG alleviates neuropathic pain by suppressing the activation of neuronal Fc γ RI. These results indicate that the activation of neuronal CRP/Fc γ RI‐related signaling plays an important role in the development of neuropathic pain in chronic constriction injury (CCI) rats. The findings may provide novel insights into the neuroimmune responses after peripheral nerve injury and suggest potential therapeutic targets for neuropathic pain. Abstract : The study shows that Fc‐gamma‐receptor type I (Fc γ RI) is expressed in neurons of the dorsal root ganglion and contributes to neuroinflammation via Syk signaling. In addition, C‐reactive protein (CRP) activates neuronal Fc γ RI/Syk‐related signals. Targeting CRP/Fc γ RI/Syk may be effective for the treatment of neuropathic pain.